Last lion : the fall and rise of Ted Kennedy - By the Team at the Boston Globe: Bella English, Neil Swidey, Jenna Russell, Sam Allis, Joseph P. Kahn, Susan Milligan, Don Aucoin Edited by Peter S. Canellos; English, Bella; Canellos, Peter S.; Globe Newspaper Co. (New York : Simon & Schuster, 2009)
Dismissed as a spent force in politics by the time he reached middle age, Ted Kennedy became the most powerful senator of the last half century and the nation's keeper of traditional liberalism. Perceptive and carefully reported, drawing heavily from candid interviews with the Kennedy family and inner circle, "Last Lion" captures magnificently his life and historic achievements, as well as the personal redemption that he found.
Includes bibliographical references (p. [415]-464).
Keywords: Kennedy, Edward Moore, -- 1932-; United States. -- Congress. -- Senate -- Biography; Legislators -- United States -- Biography